Professional Improvement of Counseling Skills Through Helping Relationship Techniques for Islamic Counseling Students - Fauziah Fauziah; Fahrul Razi (AT-TURATS, 2021)
The purpose of this research is to train the counseling skills of BKI study program students, have professionalism in conducting the process of guidance and counseling activities and conducting religious guidance, through the development of hypothetical model helping relationship. To assess their ability to use this technique researchers directed students to carry out the process of individual guidance and counseling activities through online videos that they share with youtube channel. This is done to address the inequality of conditions during this pandemic or covid-19, does not allow us to conduct activities online. The research method used in this research is research and development (RD). Theuse of this method, is based on a study in the application of models resulting from rational validation and the development of theory, to produce the right model in improving the professionalism of counseling skills of BKI students through helping relationship techniques. The results of this hypothetical model development research contribute to the improvement, professionalism of skills of student counselors proram islamic counseling guidance (BKI) in an effort to meet the standards of competence of graduates, as supervisors/ religious counselors in the community and advisers / educational counselors in schools/ madrasah.